2021
DOI: 10.3390/sports9090119
|View full text |Cite
|
Sign up to set email alerts
|

Drop-Set Training Elicits Differential Increases in Non-Uniform Hypertrophy of the Quadriceps in Leg Extension Exercise

Abstract: The study aimed to compare the effects of drop set resistance training (RT) versus traditional RT on markers of maximal muscle strength and regional hypertrophy of the quadriceps femoris. Sixteen recreationally active young men had one leg randomly assigned to the drop-set method (DS) and the other to training in a traditional manner (TRAD). Participants performed unilateral seated leg extensions using a periodized approach for eight weeks. Rectus femoris (RF) and vastus lateralis (VL) muscle thickness (MT), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Previous studies have shown non-uniform hypertrophy in the quadriceps in response to resistance exercise ( Narici et al, 1996 ). Recently, drop sets were reported to induce greater gains in hypertrophy for the rectus femoris, but not vastus lateralis, compared with traditional resistance exercise training ( Varović et al, 2021 ). Consequently, we cannot exclude the possibility of regional differences in hypertrophy within or between muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown non-uniform hypertrophy in the quadriceps in response to resistance exercise ( Narici et al, 1996 ). Recently, drop sets were reported to induce greater gains in hypertrophy for the rectus femoris, but not vastus lateralis, compared with traditional resistance exercise training ( Varović et al, 2021 ). Consequently, we cannot exclude the possibility of regional differences in hypertrophy within or between muscles.…”
Section: Discussionmentioning
confidence: 99%
“…A ration-ale for how this phenomenon may occur in DS is not readily apparent. Of note, both Varovic et al (32) and Enes et al ( 8) observed similar regional changes across the length of the vastus lateralis between conditions. Whether differential findings may be explained by differences in structural attachments between the rectus femoris and vastus lateralis (biarticular vs monoarticular, respectively) warrants further investigation.…”
Section: Hypertrophymentioning
confidence: 64%
“…Moreover, we did not detect appreciable evidence of heterogeneity between studies for the hypertrophy outcomes (I2 = 0%). Analysis of outliers identified the muscle thickness comparison of the rectus femoris at 30% muscle length in the study by Varovic et al (32) as being potentially influential; however, leave-one-out analysis showed its exclusion did not result in an appreciable difference in results.…”
Section: Meta-analytic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figs. 1 and 2 and elsewhere [ 33 ], CARE technology can automate the eccentric overload and drop setting, which are training strategies known to increase muscle size and strength [ 2 , 4 , 15 , 64 , 65 , 91 , 92 ]. Importantly, we do not propose that CARE machines necessary replace other types of resistance exercise equipment.…”
Section: Limitations Of Care Technologymentioning
confidence: 99%